The role of relational resilience in teachers’ career-long commitment and effectiveness - Gu, Qing (Taylor & Francis, 2014)
At a time when the contemporary landscape of teaching is populated with successive and persisting government policy reforms that have increased teachers’ external accountabilities, work complexity, and emotional workload, understanding why and how many teachers are able to sustain their capacity to be resilient and continue to work for improvement is an important quality retention issue. The purpose of this paper is to build upon but take further current understanding of resilience in teachers by exploring in greater depth the nature of resilience in teachers as a relational concept and the ways in which it may be related to the learning and achievement of their pupils. The empirical basis of the paper draws upon analyses of twice yearly semi-structured face-to-face interview data from 300 teachers in different phases of their careers in 100 primary and secondary schools in England over a consecutive three-year period. Through these analyses, the paper contributes additional empirical evidence to the emerging but still limited literature on the factors which influence teachers’ capacity to be resilient. The paper concludes with a consideration of the implication of the findings for the quality retention of teachers.